Unger's guide to the Bible - Unger, Merrill Frederick, 1909-1980 (Wheaton, IL Tyndale, 1974)
Contents : Bible survey, Bible dictionary, Bible concordance and Bibleland maps.
Donated by Engadine Bible Centre, 2005
Keywords: Bible -- introductions